La vida en un laboratorio de alta seguridad biológica - Sanchez-vizcaíno Rodríguez, J. M.; Mur Gil, L. (Revista Complutense de Ciencias Veterinarias, 2008)
To work and research with some kind of microorganism could suppose a high risk for humans, animals and environment. This fact makes necessary the existence of biosafety laboratories. In this type of centres, high security conditions are very strict and that could affect people who work daily inside it. Knowing how it affects them is the main objective of our study. For that reason we have done a survey to know the impressions of people who work in laboratories of Biosafety level 3 (BSL-3) . After analyzing the results of this survey, we could say that working inside BSL-3 implies certain limitations for people who work inside them, but they respect and value the importance of this security conditions.